Has India emerged? Business cycle stylized facts from a transitioning economy - Chetan Ghate; Radhika Pandey; Ila Patnaik (Indian Council for Research on International Economic Relations (ICRIER), 2012)
This paper presents a comprehensive set of stylised facts for business cycles in India from 1950-2010. We show that most macroeconomic variables are less volatile in the post reform period, even though the volatility of macroeconomic variables is still high and similar to other emerging market economies. Consistent with other emerging market economies, consumption volatility has gone up, a result that is robust to a variety of specifications. In terms of co-movement and persistence however, India looks more similar to advanced economies, and less like other emerging market economies. We argue that these changes are driven primarily by structural changes caused by liberalization policy, and not by "good luck".
Keywords: E10; E32; 330; Emerging Market Business Cycle Models; Structural Change; India's Economic Reforms; Good Luck Hypothesis; Wirtschaftswachstum; Konjunktur; Strukturwandel; Wirtschaftsreform; Indien